Factors Affecting the Level of Exhaustion among Public School Teachers in Catbalogan City - Eleanor A. Aler (Future Science / FSH-PH Publications, 2024)
Teachers' exhaustion is a prevalent issue that affects their well-being and job performance. It is crucial for educational institutions and policymakers to address these factors and implement strategies to support and prioritize the well-being of teachers. Teaching is a demanding profession that requires high levels of energy and commitment. The study aimed to assess the factors affecting the level of exhaustion of single and married teachers in public schools in Catbalogan City Division. This study utilized a descriptive-correlational research design. Accordingly,